2018
DOI: 10.3389/fnagi.2018.00391
|View full text |Cite
|
Sign up to set email alerts
|

A Ketogenic Diet Improves Cognition and Has Biochemical Effects in Prefrontal Cortex That Are Dissociable From Hippocampus

Abstract: Age-related cognitive decline has been linked to a diverse set of neurobiological mechanisms, including bidirectional changes in proteins critical for neuron function. Importantly, these alterations are not uniform across the brain. For example, the hippocampus (HPC) and prefrontal cortex (PFC) show distinct patterns of dysfunction in advanced age. Because higher cognitive functions require large–scale interactions across prefrontal cortical and hippocampal networks, selectively targeting an alteration within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 103 publications
10
103
0
Order By: Relevance
“…In this study, we have replicated previous data showing that biconditional association tasks are particularly sensitive behavioral assays for detecting age-related cognitive decline relative to the Morris watermaze [20,35]. Furthermore, we observed that both males and females showed similar performance declines across age on the Similarly, we found no differences in spatial memory recall during Morris watermaze testing and, as previously reported in rats of this strain and age, no age differences either [20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we have replicated previous data showing that biconditional association tasks are particularly sensitive behavioral assays for detecting age-related cognitive decline relative to the Morris watermaze [20,35]. Furthermore, we observed that both males and females showed similar performance declines across age on the Similarly, we found no differences in spatial memory recall during Morris watermaze testing and, as previously reported in rats of this strain and age, no age differences either [20].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the arms of the maze had an asymmetry, such that only the right arm was enclosed while the animals were relatively more exposed on the middle and left arms. This asymmetry biases rats to alternate towards the closed 'safe' arm [35]. To dampen the influence of extraneous noise on behavior, a white noise machine was used during behavioral training and testing.…”
Section: Apparatus and Habituationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cerebral glucose metabolism declines with age, the ability to utilize ketone bodies for energy production does not (Castellano et al, 2015;Cunnane et al, 2016;Lying-Tunell et al, 1981;Ogawa et al, 1996). Therefore, the potential to bypass impaired glycolysis through the elevation of ketone body synthesis and promotion of fat oxidation may alter the expression of hippocampal synaptic signaling-related genes (Hernandez et al, 2018a) to ultimately improve cognitive function (Hernandez et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Ketogenic diets have been utilized to alter neuronal signaling patterns in patients with epilepsy for almost a century (Freeman et al, 1998). More recent evidence indicates that it can alter both excitatory and inhibitory signaling-related proteins within young and aged brains (Hernandez et al, 2018a(Hernandez et al, , 2018b.…”
Section: Introductionmentioning
confidence: 99%